Soft solution in situ synthesis of chitosan/iron oxide nanocomposites and their magnetic properties - Vaewbundit, Sukanda; Siriphannon, Punnama (My University, 2021)
Chitosan/iron oxide nanocomposites (CS/IO) were synthesized by using soft solution in situ synthesis. An aqueous mixture of iron(ii), iron(iii) and chitosan was added drop by drop to a solution of a sodium tripolyphosphate crosslinker with stirring for 30 min, resulting in in situ ionically crosslinked chitosan, with incorporated Fe2+ and Fe3+ (CS/Fe2+Fe3+). The CS/Fe2+Fe3+ precursors were then treated in alkaline solution by two different methods, i.e. hydrothermal and refluxing, where the Fe2+ and Fe3+ ions reacted to form quasi-spherical magnetite-maghemite nanocrystals in the constrained space of the crosslinked chitosan CS/IO nanocomposites. The pressurized hydrothermal system promoted the growth of iron oxide nanocrystals, leading to slightly larger crystallites (3.9-4.3 nm), compared to 3.9 nm from the refluxing system. The iron oxide crystallites also became smaller with increased crosslinking density of the chitosan matrix. The resultant CS/IO nanocomposites exhibited superparamagnetism with Mmax in the range of 9.6-15 emu g-1 and low coercivity and magnetic remanence. In addition, they showed high cell viability, 82-96%, indicating them as potential candidates for medical applications.